استخدام أنظمة التحكم الحديثة لأتمتة المعابر السطحية للخطوط الحديدية السورية - مخول, مخائيل; محمود, علي; سعد, أسامه احمد (Latakia University Journal -Engineering Sciences Series, 2014)
يهدف هذا البحث إلى تطوير آلية التحكم بالمعابر السطحية في الخطوط الحديدية التي تدار يدوياً, بالاعتماد على أنظمة التحكم الحديثة التي تتضمن المتحكمات والمعالجات الصغرية وأجهزة التحسس والمشغلات والاتصالات والبرمجيات لتشكيل نظم مؤتمتة ذكية يمكن مراقبتها عن بعد. تم وضع خوارزمية التحكم والمخططات الصندوقية لكافة الوظائف عند المعبر السطحي بالاعتماد على المعايير الأوروبية(Safer European Level Crossing Appraisal and Technology, SELCAT) التي تُعنى بتطوير تقنيات الأمان في المعابر السطحية الأوروبية. تم في هذا المقال تصميم برنامجٍ يحاكي جميع الإجراءات والتحذيرات الموجودة عند المعبر السطحي الحقيقي بالاعتماد على لغة البرمجة الرسومية (Laboratory Virtual Instrumentation Engineering Workbench, LabVIEW) مع إمكانية المراقبة عن بعد عبر شبكة تراسل المعطيات من قبل سائق القطار أو المحطة, وتمكننا من تحديد اقتراب القطار من المعبر بدقة أكبر باستخدام الطريقة المؤتمتة, وتأمين كافة التنبيهات والحماية اللازمة لمستخدمي الطريق وسائق القطار, وبالتالي زيادة الأمان وتقليل حوادث التصادم بين السيارات والقطار. This research aims to develop the control process of manned railway level crossings depending on the modern control systems that contain microcontrollers, microprocessors, sensors, actuators, communications and software to compose smart automated systems that could be remotely monitored. The control logarithm and flow charts for all the functions that occur on the railway level crossing were used, depending on European standards (Safer European Level Crossing Appraisal and Technology, SELCAT) that aim to develop safety technologies on European railway level crossings. We designed a program to emulate all warnings and procedures that happen on the real railway level crossing, depending on the graphical Programming language (Laboratory Virtual Instrumentation Engineering Workbench, LabVIEW) that insures local monitoring on the crossing, and remote monitoring at the station and on the train via data network. By using the automated method, we were able to determine the approaching train to the crossing precisely, and insuring the provision of all warnings to road users and train driver to increase safety and reduce collision accidents between automobiles and train.